Time scale analysis of enzymatic reduction of uric acid in a microfluidic biomedical device - Asgharpour Masouleh, Alireza; Pantakitcharoenkul, Jaturavit; Coblyn, Matthew; Plazl, Igor; Jovanovic, Goran N. (Frontiers in Chemical Engineering, 2024)
Time Scale Analysis(TSA) is an investigative tool used in engineering design to identify locations in processes that should be a focus of Process Intensification(PI).TSA points to process variables & parameters that could be used to advance and measure PI improvement.However,TSA cannot suggest any specific design solution to intensify process performance.Instead,design engineers should use their fundamental knowledge and creative intelligence to specify detailed design transformations.TSA will then provide a specific quantitative measure of the improvement.TSA implementation improves an explicitly defined process performance,thus helping achieve PI goals.TSA is based on first principles,and it utilizes Characteristic Times(CT) such as diffusion,mean residence,and reaction times to improve an existing process.In this study,we specifically consider microfluidic biomedical devices.To illustrate the genesis of CTs and TSA,we start by developing a mathematical model of an enzymatic degradation process in a biomedical device called iCore based on mass,momentum,and kinetic equations.After introducing user-defined scaling parameters,we extract CTs pertinent to the enzymatic degradation of uric acid in this device.Diffusion coefficients,microchannel architectural characteristics,hydrogel thickness,and characteristic parameters of enzyme kinetics are the parameters and process variables incorporated in this analysis.Finally,we compared the extracted CTs with a COMSOL parametric study to demonstrate how TSA as a design tool and adjusting design parameters,such as diffusion coefficient can enhance the enzymatic reaction process without a need for complex computational modeling.It's crucial to recognize that Pertinent CTs can be determined by understanding the type and nature of the observed process,published data, and other foundational engineering design work.There is no need for mathematical modeling and numerical simulations to identify and acknowledge the CTs relevant and essential to the observed process;in this work,we only illustrate the principal origin of CTs via a detailed mathematical model of the process,as previously reported by Jovanovic et al.Therefore,in a routine application of TSA,it's important to remember that mathematical modeling and detailed numerical simulations are not necessary.The investigations on how best to apply TSA in higher level design functions such as PI,scale-up & numbering-up,change of device architecture,change of operating conditions,change of process feed characteristics,change of material physical and chemical properties,parametric optimization of the system for various objective functions,and techno-economic analysis,are yet to be studied.